Pengaruh Advertising, Capital Expenditure, Pendidikan CEO, Pendidikan CFO dan Karakter Eksekutif Terhadap Tax Avoidance - Yani, Sari Putri; Hamdani, Hamdani; Hidayat, Imam; Abbas, Dirvi Surya (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to determine the influence of advertising, capital expenditure, CEO education, CFO education, and executive character on tax avoidance. The study period used is from 2019 to 2023. The study population includes financial sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling technique used is purposive sampling, utilizing the Eviews 12 data analysis program. Based on the established criteria, 8 companies were identified as meeting the criteria. The analysis method used was panel data regression analysis. The results of this study indicate that advertising and capital expenditure partially influence tax avoidance, CEO education partially influences tax avoidance, CFO education does not partially influence tax avoidance, and executive character does not partially influence tax avoidance.